An Evaluation of the Biocompatibility and Chemical Properties of Two Bioceramic Root Canal Sealers in a Sealer Extrusion Model of Rat Molars - Shintaro Takahara; Naoki Edanami; Razi Saifullah Ibn Belal; Kunihiko Yoshiba; Shoji Takenaka; Naoto Ohkura; Nagako Yoshiba; Susan Gomez-Kasimoto; Yuichiro Noiri (Journal of Functional Biomaterials)
This study assessed the biocompatibility and chemical properties of two bioceramic root canal sealers, EndoSequence BC Sealer (EBC) and Nishika Canal Sealer BG (NBG), using a sealer extrusion model. Eight-week-old male Wistar rats were used. The mesial root canals of the upper first molars were pulpectomized and overfilled with EBC, NBG, or, as reference, epoxy resin-based AH Plus (AHP). After 28 days, periapical tissue reactions were assessed using microcomputed tomography and histological staining. The elemental composition and chemical composition of the extruded EBC and NBG were analyzed at Day 1 and 28 using an electron probe microanalyzer and micro-Raman spectroscopy. No periapical lesions were observed with the sealer extrusion. Additionally, inflammation around the extruded EBC and NBG was minimal to mild on Day 28, whereas moderate inflammation was found around the extruded AHP. Silicon concentration in the extruded EBC and NBG decreased significantly from Day 1 to 28, with almost no silicon present on Day 28. Furthermore, the extruded EBC and NBG became calcium- and phosphorus-rich, showing a Raman band for hydroxyapatite on Day 28. In conclusion, EBC and NBG demonstrated favorable biocompatibility and the ability to release silicon elements and produce hydroxyapatite when extruded into the periapical tissues. AHP showed moderate periapical tissue irritancy.